Job Satisfaction and Stress as Determinants of Employees’ Turnover Intention in Yogyakarta - Nila Puspita Riyandani; Yenni Kurnia Gusti (LifeSciFi, 2026)
High turnover intention among employees of Bale Ayu Restaurant Yogyakarta is reflected in frequent resignations and fluctuations in workforce numbers, a condition assumed to be influenced by both internal employee factors and the work environment. The study aims to analyze the effect of job satisfaction and job stress on employee turnover intention. This research adopts a quantitative approach using a causal associative method with SPSS 22 as the data analysis tool. The population consists of all 60 employees of Bale Ayu Restaurant Yogyakarta, and a saturated sampling technique was applied, in which the entire population was used as the sample. Data were obtained through questionnaires measured using a Likert-type scale. The findings indicate that job satisfaction has a statistically significant negative relationship with turnover intention, suggesting that employees who experience higher levels of satisfaction are less likely to intend to leave the organization. In contrast, job stress shows a significant positive relationship with turnover intention, meaning that increased work-related stress raises employees’ intentions to resign. When examined jointly, job satisfaction and job stress are found to have a significant combined effect on turnover intention among employees of Bale Ayu Restaurant Yogyakarta.